WHAT ARE SWORN TRANSLATORS PUNISHED FOR? 10 YEARS OF OPERATION OF THE COMMISSION FOR PROFESSIONAL ACCOUNTABILITY OF SWORN TRANSLATORS AT THE MINISTER OF JUSTICE - KUBACKI, Artur Dariusz; GOŚCIŃSKI, Jan (Comparative Legilinguistics, 2015)
The aim of the paper is to present the operation of the Commission for Professional Accountability of Sworn Translators at the Minister of Justice looking back on its almost ten-year history. In the theoretical part, we will discuss the legal framework within which it operates, the procedure it follows and the types of penalties it may impose. In the practical part, we will carry out a quantitative and qualitative analysis of the cases which have been heard so far at hearings conducted before the Commission. The analysis will allow us to distinguish different types of infringements committed by sworn translators. We will focus our attention on translation errors, especially those which had or might have had adverse legal consequences.